2009
DOI: 10.1017/s1742170509990081
|View full text |Cite
|
Sign up to set email alerts
|

Soilless cultivation for high-quality vegetables with biogas manure in China: Feasibility and benefit analysis

Abstract: Vegetables, the indispensable staple produce providing humans with many beneficial substances, are readily contaminated by nitrate, heavy metals and pesticides during conventional cultivation. In particular, off-season vegetables grown in protected systems with low light intensity do tend to accumulate more nitrate in tissues due to excess N fertilization driven by farmers' desire for high yields. Over-the-limit accumulation of the harmful substances in vegetables constitutes a serious hazard to human health g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…Liu et al [39] reported that biogas manure is an effective nutrient source for high-quality vegetable production, based on synergistic effects and its ability to enhance yield and improve quality, and to suppress nitrate accumulation. In the present study, application of PS combined with nitrogen fertilizer decreased the processing quality of direct-seeding rice only slightly, but in our previous study, Gao et al [28] found that application of PS to machine-transplanted rice enhanced brown, milled and head milled rice.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [39] reported that biogas manure is an effective nutrient source for high-quality vegetable production, based on synergistic effects and its ability to enhance yield and improve quality, and to suppress nitrate accumulation. In the present study, application of PS combined with nitrogen fertilizer decreased the processing quality of direct-seeding rice only slightly, but in our previous study, Gao et al [28] found that application of PS to machine-transplanted rice enhanced brown, milled and head milled rice.…”
Section: Discussionmentioning
confidence: 99%
“…Under soilless conditions, digestates from animal slurries are an effective nutrient source in vegetable production. Undiluted digestates with high electrical conductivity are not suitable . The key problems obstructing their application in soilless culture are the variability of components and the imbalance in the elemental composition .…”
Section: Digestates As Fertilizers For Vegetable Cropsmentioning
confidence: 99%
“…Under soilless conditions, digestates from animal slurries are an effective nutrient source in vegetable production. Undiluted digestates with high electrical conductivity are not suitable [29].…”
Section: Digestates As Fertilizers For Vegetable Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-quality vegetables can be produced in protected facilities. Liu et al [6] defined high-quality vegetables as vegetables not containing over-the-limit harmful substances (nitrate, nitrite, heavy metals and pesticides), and not having negative effects on human health after ingestion. Health-beneficial phytochemicals of vegetables are referred to some substances, such as ascorbic acid, carotenoids, phenolics, flavoids, which are influential beneficially to human health.…”
Section: Introductionmentioning
confidence: 99%